2009
DOI: 10.1308/003588409x359006
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Support Received from Breast Care Nurses by Depressed Patients Following a Diagnosis of Breast Cancer

Abstract: Ann R Coll Surg Engl 2009; 91: 43-45 43Maguire et al. 1 were the first to show that a specialist nurse could reduce psychological morbidity following diagnosis of breast cancer, and the role of the breast care nurse (BCN) was developed in response. Further evaluation confirmed that the BCN can identify patients at risk of distress and provide effective emotional support.2-5 As a third or more of patients are clinically depressed or anxious immediately after diagnosis, 6-8 the BCN is now a key member of the bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The value of cancer specialist nurses has also been demonstrated in providing emotional support and advocacy (Ambler et al . 1999; The London and South East Lung Cancer Forum for Nurses 2004; Lewis & Anthony 2007; Worster & Holmes 2008), supporting depressed patients (Clark et al . 2009), liaising with other professionals to ensure coordinated care (Amir et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of cancer specialist nurses has also been demonstrated in providing emotional support and advocacy (Ambler et al . 1999; The London and South East Lung Cancer Forum for Nurses 2004; Lewis & Anthony 2007; Worster & Holmes 2008), supporting depressed patients (Clark et al . 2009), liaising with other professionals to ensure coordinated care (Amir et al .…”
Section: Discussionmentioning
confidence: 99%
“…A review of studies of nurse-patient interactions in cancer care found evidence that specialist nurses are very effec-tive information providers for cancer patients and that patients may prefer nurses as information providers at specific stages of their treatment and especially concerning symptom management (Koutsopoulou et al 2010). The value of cancer specialist nurses has also been demonstrated in providing emotional support and advocacy (Ambler et al 1999; The London and South East Lung Cancer Forum for Nurses 2004; Lewis & Anthony 2007;Worster & Holmes 2008), supporting depressed patients (Clark et al 2009), liaising with other professionals to ensure coordinated care (Amir et al 2004;The London and South East Lung Cancer Forum for Nurses 2004;Tarrant et al 2008;Ream et al 2009) and providing continuing support after discharge from hospital (Griffiths et al 2007).…”
Section: Professional-patient Communicationmentioning
confidence: 99%
“…Reasoning that effective clinical relationships need positive images of both self and other [12], we predicted that, as in mental health care [13], patients reporting the strongest relationships with their surgeons would be those with secure attachment. Clinical relationships in cancer care are compromised by patients' depression [14] which can be associated with attachment style [15] and which we therefore measured as a possible confounding variable.…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, the expert panel considered that psychological care should be multidisciplinary (Agreement: 100 %; LE/DR: √). The ABCCN should pay attention to psychological considerations for patients and their families throughout the process, and engage in good communication with them, providing appropriate information at each point in the process (Agreement: 100 %; LE/DR: 4/D) [9, 15, 16]. Also, it is recommended that the ABCCN monitors patients’ anxiety levels, so that psychological abnormalities that must be addressed by mental health professionals could be early detected (Agreement: 100 %; LE/DR: 4/D) [17].…”
Section: Resultsmentioning
confidence: 99%